High-efficiency passivated emitter and rear cells with nano honeycomb structure. (August 2021) - Pu, Tian; Shen, Honglie; Hong Neoh, Kuang; Gao, Kai; Ye, Fei
Highlights: A light-trapping nano honeycomb structure was prepared on a c-Si wafer surface. The honeycomb structure showed excellent reflectance and passivation. An efficiency of 22.80% was achieved in PERC cell with honeycomb structure. Efficiency gain of 0.3% was obtained compared with normal upward pyramid texture. Abstract: In this paper, a light-trapping nano honeycomb (NH) structure with a polyhedral interior was prepared on a c-Si wafer surface, which has a much lower reflectance and better passivation effect than that of a pyramid-textured surface. The NH structure was prepared using the metal-assisted chemical etching method together with the nanostructure rebuilding (NSR) method. Through reflectance measurement, internal quantum efficiency characterization and finite-difference time-domain simulation, the advantages of the NH structure were systematically studied. The formation mechanism of the NH structure was considered to be due to both the anisotropic and isotropic etching properties of Si crystal, and its main affecting factor was the NSR reaction time. To further demonstrate its potential in monocrystalline silicon cells, passivated emitter and rear cells (PERC) using NH-textured c-Si wafers were fabricated. A high efficiency of 22.80% was achieved, which was 0.3% and 0.16% higher compared to the normal upward pyramid-textured PERC and the inverted pyramid-textured PERC, respectively. The NH structure is expected to have a great potential application in the mass production of c-Si solar cells.